African genes - Hopkins, W.
Are black Africans genetically predisposed to be better athletes? Ferret found the best perspective yet on this question from a chapter in Peak Performance, a new paperback on sports training and nutrition. The average African may be no different from the average non-African, but there's probably a greater diversity of athletic talent among Africans. The evidence comes from recent research comparing the frequency of different variants of the same stretch of DNA in various populations. Non-Africans have less variants, presumably because their forebears migrated out of Africa as a small group with only a small sample of genes from the African gene pool. The researchers didn't look at DNA coding for athleticism, but there's little doubt it will also be more diverse in Africans. With more genes to choose from, nature can build a better athlete from African stock. So, give enough Africans the opportunity to play a given sport and it's inevitable one will emerge with the right genes to win the Olympic gold. And it won't end with sport: expect Africans to excel in every field of human endeavor during the next millennium.